EVALUASI PROGRAM RUMAH SUBSIDI BAGI MASYARAKAT BERPENGHASILAN RENDAH (MBR) DI KABUPATEN BULELENG - Cahyaninghati, Ruth; Sudharsana, I Made Gede; Kardinal, Ni Gusti Ayu Diah Ambarwati (UNIVERSITAS PENDIDIKAN GANESHA, 2021)
Buleleng Regency is a district that has a very high housing backlog compared to other districts in Bali Province. The government provides subsidized housing assistance to low-income communities with the assistance of FLPP. The implementation of the subsidized housing program with FLPP assistance in Buleleng Regency has been running for 5 years. The purpose of this study is to determine the implementation of the subsidized housing program in Buleleng Regency and to determine the level of housing feasibility for subsidized houses. This study used a descriptive research method with a qualitative approach and supported by quantitative data obtained through interviews and parameters of each aspect of the feasibility level of the house, interviews and observations. The data will be analyzed using descriptive analysis method. Based on the results of the study, it was concluded that in implementing the subsidized housing with the FLPP program, it was right on target for low-income people, in accordance with the conditions set by the government and was livable even though for the long term this house was not very helpful due to the inadequate area of the house